Distribution and Composition of Waste on the Coast of Gili Trawangan - Sabilillah, Sabilillah; Larasati, Chandrika Eka; Virgota, Arben (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The coastal area of Gili Trawangan, a prominent tourism destination, is facing increasing ecological pressure due to intensified tourism activities and population growth. This study aims to analyze the distribution and composition of macro debris along the coast of Gili Trawangan, North Lombok Regency. This study used transect and quadrat methods, as well as marine debris classifications according to NOAA and Tangavoa Blue. The results showed that the highest amount of waste was plastic (71%), followed by glass (13%), and ceramics (8%). The highest waste distribution was found at the port (62kg) and tourist areas (30%). These findings highlight that inadequate waste management and low public awareness significantly contribute to coastal pollution. Therefore, an integrated waste management strategy and increased public participation are urgently needed to preserve the marine ecosystem of Gili Trawangan.